Customer Discrimination and Employment Outcomes: Theory and Evidence from the French Labor Market - Pierre-Philippe Combes; Bruno Decreuse; Morgane Laouénan; Alain Trannoy (Institute for the Study of Labor (IZA), 2014)
The paper investigates the link between the over-exposure of African immigrants to unemployment in France and their under-representation in jobs in contact with customers. We build a two-sector matching model with ethnic sector-specific preferences, economy-wide employer discrimination, and customer discrimination in jobs in contact with customers. The outcomes of the model allow us to build a test of ethnic discrimination in general and customer discrimination in particular. We run the test on French individual data in a cross-section of local labor markets (Employment Areas). Our results show that there is both ethnic and customer discrimination in the French labor market.
Keywords: J15; J61; R23; 330; discrimination; matching frictions; jobs in contact; ethnic unemployment; local labor markets